2019
DOI: 10.1139/cjc-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in carbon–carbon coupling reactions at palladium(IV) and platinum(IV)

Abstract: The isomerization and reductive elimination reactions from octahedral organometallic complexes of palladium(IV) and platinum(IV) usually occur through five-coordinate intermediates that cannot be directly detected. This paper reports a computational study of five-coordinate complexes of formulae [PtMe3(bipy)]+, [PtMe2Ph(bipy)]+, and [PtMe(CH2CMe2C6H4)(bipy)]+ (M = Pd or Pt, bipy = 2,2′-bipyridine), particularly with respect to reactivity and selectivity in reductive elimination. All of the complexes are predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In a 2008 report, Goldman, Krogh-Jespersen, and co-workers highlighted a second key controlling factor in the selectivity of reductive elimination reactions in addition to hybridization: the importance of aryl orientation in reductive elimination. This important consideration has received more attention in recent years, and several researchers have taken aryl orientation into account in their analyses of C–C bond formation preferences. ,, Both the orientation of the aryl ring and the conformational flexibility of the ligand appear to play a crucial role in C–C reductive elimination selectivity.…”
mentioning
confidence: 99%
“…In a 2008 report, Goldman, Krogh-Jespersen, and co-workers highlighted a second key controlling factor in the selectivity of reductive elimination reactions in addition to hybridization: the importance of aryl orientation in reductive elimination. This important consideration has received more attention in recent years, and several researchers have taken aryl orientation into account in their analyses of C–C bond formation preferences. ,, Both the orientation of the aryl ring and the conformational flexibility of the ligand appear to play a crucial role in C–C reductive elimination selectivity.…”
mentioning
confidence: 99%
“…In related complexes [PtXMe 2 R(NN)], X = halogen, NN = diamine ligand, it is generally found that the bulkier alkyl group R prefers the axial coordination site trans to X, so complex 4 behaves in the expected way with 4b preferred over 4a when hydrogen bonding is not present. 19,20,30 The DFT calculations do not consider intermolecular interactions, so the quantitative aspects should be considered with caution, but the predictions do support the experimental observations in a qualitative way.…”
Section: Resultsmentioning
confidence: 99%
“…Reductive elimination (RE) reactions are part of important catalytic processes. RE with concomitant C–C cross-coupling plays a key role in the synthesis of organic molecules, including natural products and drugs. RE from organometallic d 6 -configured octahedral Pt­(IV) and Pd­(IV) complexes with the concomitant formation of alkanes by Csp 3 –Csp 3 cross-coupling has been extensively studied, while investigations on homo-coupling reactions are scarce. …”
Section: Introductionmentioning
confidence: 99%